Serum Spot 14 concentration is negatively associated with thyroid-stimulating hormone level. Issue 40 (October 2016) - Chen, Yen-Ting; Tseng, Fen-Yu; Chen, Pei-Lung; Chi, Yu-Chao; Han, Der-Sheng; Yang, Wei-Shiung
Abstract : Abstract: Spot 14 (S14) is a protein involved in fatty acid synthesis and was shown to be induced by thyroid hormone in rat liver. However, the presence of S14 in human serum and its relations with thyroid function status have not been investigated. The objectives of this study were to compare serum S14 concentrations in patients with hyperthyroidism or euthyroidism and to evaluate the associations between serum S14 and free thyroxine (fT4) or thyroid-stimulating hormone (TSH) levels. We set up an immunoassay for human serum S14 concentrations and compared its levels between hyperthyroid and euthyroid subjects. Twenty-six hyperthyroid patients and 29 euthyroid individuals were recruited. Data of all patients were pooled for the analysis of the associations between the levels of S14 and fT4, TSH, or quartile of TSH. The hyperthyroid patients had significantly higher serum S14 levels than the euthyroid subjects (median [Q1, Q3]: 975 [669, 1612] ng/mL vs 436 [347, 638] ng/mL, P  < 0.001). In univariate linear regression, the log-transformed S14 level (logS14) was positively associated with fT4 but negatively associated with creatinine (Cre), total cholesterol (T-C), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and TSH. The positive associations between logS14 and fT4 and the negative associations between logS14 and Cre, TG, T-C, or TSH remained significant after adjustment with sex and age. These associations were prominent in females but not in males. The logS14 levels were negatively associated with the TSH levels grouped by quartile (ß = −0.3020, P  < 0.001). The association between logS14 and TSH quartile persisted after adjustment with sex and age (ß = −0.2828, P  = 0.001). In stepwise multivariate regression analysis, only TSH grouped by quartile remained significantly associated with logS14 level. We developed an ELISA to measure serum S14 levels in human. Female patients with hyperthyroidism had higher serum S14 levels than the female subjects with euthyroidism. The serum logS14 concentrations were negatively associated with TSH levels. Changes of serum S14 level in the whole thyroid function spectrum deserve further investigation.